Description of three new species of Eumida Malmgren, 1865 (Phyllodocidae, Annelida) from Southern and Southeastern Brazil - De Oliveira, Verônica Maria; Eibye-Jacobsen, Danny; Lana, Paulo da Cunha (Zootaxa, 2015)
We describe three new species of Eumida from shallow estuarine and shelf bottoms from south and southeastern Brazil as part of a regional survey of the family Phyllodocidae. Previous regional records of Eumida sanguinea (Örsted, 1843) are herein referred to Eumida dracodermica sp. nov. The two species differ in the size of the prostomium, the distribution of micropapillae on the proboscis, and the shape of the dorsal cirri. Eumida macrophthalma sp. nov. has much larger eyes than the other two species described herein. The dorsal cirri on anterior median segments are rounded and on median and posterior segments they are asymmetrical and cordiform, longer than the dorsal cirri in Eumida dracodermica sp. nov. The lanceolate median dorsal cirri in Eumida delicata sp. nov. are only shared with E. ockelmanni Eibye-Jacobsen, 1987. It is also possible to diagnose the three species by their dorsal whitish pigmentation patterns on the first segments of living or well conserved animals
World Polychaeta Database (WPolyDb)